Brain tumor detection through image processing - Azmim, Tahaziba; Shumon, Azizul Hakim chy.; Alam, Maksud; Mishu, Saurav Ahmed; Chowdhury, Nuhash Ahmed (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.